Implementasi Model Problem-Solving untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan - Putri, Febby Latifah; Dewi, Citra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to determine the improvement of student learning outcomes and implement the learning that results in active students in the Basic Electricity Engineering subject of SMK Negeri 2 Payakumbuh students through the application of Problem-Solving. This research uses research genes in the form of Pre-Experimental Design with One Group Prestest-Posttest. This study uses research instruments pretest and posttest questions in the objective form to see the learning outcomes of students and tested using a validity test, reliability test, differentiation test, and question difficulty index to determine the feasibility of the instruments used. The results showed an increase in student understanding by using the Problem-Solving learning model compared to conventional learning. Student learning outcomes after applying the Problem-Solving model are improved, so the Problem-Solving model has a positive impact in improving student learning outcomes. However, it should be noted that this study has some limitations, such as limited coverage to one school and one subject. Further studies involving more schools and subjects can provide greater insight into the application of this Problem-Solving learning model.